Case report: The use of Venovenous Extracorporeal Membrane Oxygenation in the Treatment of Acute Respiratory Distress Syndrome in Severe Leptospirosis - Silva Neto, Fernando de Oliveira e; Diniz, Renan Gomes Mendes; Chagas, Gabriel Cavalcante Lima; Felix, Helen Melo Oliveira; Ximenes, Ana Larissa Pedrosa; Carvalho, Bráulio Matias de; Oliveira, Fátima Rosane de Almeida; Trompieri, Daniel Francisco de Mendonça; Meija, Juan Alberto Casquillo; Andrade, Lucia da Conceição; Daher, Elizabeth de Francesco (Brazilian Journal of Case Reports, 2024)
Leptospirosis is a globally distributed zoonosis with a clinical spectrum ranging from mild febrile illness to life-threatening disease, that can result in acute kidney injury (AKI) and severe pulmonary complications such as alveolar hemorrhage and acute respiratory distress syndrome (ARDS). We present the case of a 20-year-old man with fever and respiratory distress, diagnosed with ARDS and AKI. Venovenous (VV), extracorporeal membrane oxygenation (ECMO) and sustained low-efficiency daily dialysis (SLED) were initiated. The patient showed significant respiratory improvement after eight days and renal recovery after seventeen days. Leptospirosis serological conversion confirmed the diagnosis. This case highlights the potential of VV ECMO as an effective supportive therapy in severe respiratory failure secondary to leptospirosis. Early recognition and aggressive management, including ECMO and daily dialysis, may enhance outcomes in severe pulmonary leptospirosis.